Effects of high-intensity interval training in combination with detraining on mental health in women with polycystic ovary syndrome: A randomized controlled trial - Santos, Isis K.; Pichini, Gabriel S.; Daniel d. Ferreira, Carlindo; Dantas, Pedro B.; Browne, Rodrigo A. V.; de Queiros, Victor; Soares, Gustavo M.; Gonçalves, Ana K.; Cabral, Breno G.; Maranhão, Tecia Maria O.; Dantas, Paulo Moreira S. (Frontiers in Physiology, 2022)
Purpose: To investigate the effects of High Intensity Interval Training (HIIT) and Detraining on quality of life and mental health in women with Polycystic Ovary Syndrome (PCOS). Methods: Twenty-three women with PCOS (aged 21-34 years) were allocated into a control group (n = 11) and a supervised HIIT group (n= 12). The 12 weeks of HIIT consisted of sessions 40-60 min in length, 3 days per week under supervision. Quality of life and mental health (using a questionnaire) were assessed. The differences in all variables, and the relative changes between baseline after 12 weeks and detraining (30 days) were investigated. Results: The participants were classified as overweight, had a high percentage of body fat and irregular menstrual cycles (amenorrhea). The HIIT group showed improvements in the domains of functional capacity (P = 0.022; ES= 1.7), physical aspects (P = 0.027; ES= 1.7), general status (P = 0.021; ES= 3.1), anxiety (P = 0.025; ES= 1.0,), and depression (P = 0.031; ES= 1.7) (pre-post). However, these improvements were not maintained after the 30-days detraining period in the domains of quality of life. Conclusion: The HIIT program promoted an improvement in quality of life and mental health in women with PCOS; additionally, it was observed that after 4 weeks of detraining there was a reduction in quality of life, however, the mental health domains (anxiety and depression) showed a stability in the HIIT group different to the control group.